Particle dynamics in spherically symmetric electro-vacuum instantons - Garnier, Arthur (The European physical journal. C, Particles and fields, 2024)
In this paper, we study the geodesic motion in spherically symmetric electro-vacuum Euclidean solutions of the Einstein equation. There are two kinds of such solutions: the Euclidean Reissner–Nordström (ERN) metrics, and the Bertotti–Robinson-like (BR) metrics, the latter having constant Kretschmann scalar. First, we derive the motion equations for the ERN spacetime and we generalize the results of Battista–Esposito, showing that all orbits in as ERN spacetime are unbounded if and only if it has an event horizon. We also obtain the Weierstrass form of the polar radial motion, providing an efficient tool for numerical computations. We then study the angular deflection of orbits in the Euclidean Schwarzschild spacetime which, in contrast to the Lorentzian background, can be either positive or negative. We observe the presence of a null and a maximal deflection rings for particles with velocity at infinity v > 1 and we give approximate values for their size when v ≳ 1 . For BR spacetimes, we obtain analytic solutions for the radial motion in proper length, involving (hyperbolic) trigonometric functions and we deduce that orbits either exponentially go to the singularity or are periodic. Finally, we apply the previous results and use algorithms related to Weierstrass’ elliptic functions to produce a Python code to plot orbits of the spacetimes ERN and BR, and draw “shadows” of the first ones, as it was already done before for classical black holes.